Caspase-11–mediated enteric neuronal pyroptosis underlies Western diet–induced colonic dysmotility - Ye, Lan; Li, Ge; Goebel, Anna; Raju, Abhinav V.; Kong, Feng; Lv, Yanfei; Li, Kailin; Zhu, Yuanjun; Raja, Shreya; He, Peijian; Li, Fang; Mwangi, Simon Musyoka; et al. (The Journal of clinical investigation, 2020)
Enteric neuronal degeneration, as seen in inflammatory bowel disease, obesity, and diabetes, can lead to gastrointestinal dysmotility. Pyroptosis is a novel form of programmed cell death but little is known about its role in enteric neuronal degeneration. We observed higher levels of cleaved caspase-1, a marker of pyroptosis, in myenteric ganglia of overweight and obese human subjects compared with normal-weight subjects. Western diet-fed (WD-fed) mice exhibited increased myenteric neuronal pyroptosis, delayed colonic transit, and impaired electric field stimulation-induced colonic relaxation responses. WD increased TLR4 expression and cleaved caspase-1 in myenteric nitrergic neurons. Overactivation of nitrergic neuronal NF-κB signaling resulted in increased pyroptosis and delayed colonic motility. In caspase-11-deficient mice, WD did not induce nitrergic myenteric neuronal pyroptosis and colonic dysmotility. To understand the contributions of saturated fatty acids and bacterial products to the steps leading to enteric neurodegeneration, we performed in vitro experiments using mouse enteric neurons. Palmitate and lipopolysaccharide (LPS) increased nitrergic, but not cholinergic, enteric neuronal pyroptosis. LPS gained entry to the cytosol in the presence of palmitate, activating caspase-11 and gasdermin D, leading to pyroptosis. These results support a role of the caspase-11-mediated pyroptotic pathway in WD-induced myenteric nitrergic neuronal degeneration and colonic dysmotility, providing important therapeutic targets for enteric neuropathy.